The effect of 5-hydroxytryptophan, a serotonin precursor, on adults with high levels of Attention Deficit Hyperactivity Disorder traits: A randomised, controlled trial - Eleanor Jackson; Timothy Riley; Paul G. Overton (PLoS ONE, 2026)
Background Although several effective therapies exist for Attention Deficit Hyperactivity Disorder (ADHD), current pharmaceutical treatment carries a high risk of misuse and high levels of discontinuation, evidencing a need for alternatives. One possible avenue is serotonergic intervention, particularly within the serotonin synthesis pathway, where there are several potential loci of dysfunction in ADHD. This study aimed to assess the efficacy of acute 5-hydroxytryptophan, a serotonin precursor, in reducing distractibility in adults with high levels of ADHD traits. Trial design and methods The study consisted of a randomised, controlled trial to assess the effects of acute 5-hydroxytryptophan administration compared to placebo. Participants consisted of individuals with high (N = 56) and low (N = 56) levels of ADHD traits, determined using the Adult ADHD self-report scale screener (ASRS v1.1), with randomised allocation to intervention or placebo in a 1:1 ratio. Both participants and investigators delivering the trial were blind to the allocation. Baseline testing of distractibility using a task-relevant (Eriksen flanker) and novel task-irrelevant (N-back coupled with an auditory stimulus) paradigm was completed, participants were given the intervention or placebo, and tasks were repeated 90 min post-administration. Results and conclusions The flanker and N-back task found few differences between individuals with high and low levels of ADHD traits, and the N-back task did not produce a distractor effect as initially predicted. 5-hydroxytryptophan produced no significant positive effect in any measure of distractibility that differed between individuals with high or low ADHD traits. Only accuracy on silent trials in the N-back task was affected by 5-hydroxytryptophan administration: placebo participants showed an improvement in performance and 5-hydroxytryptophan-administered participants did not. 19.6% of participants in the 5-hydroxytryptophan group experienced adverse events of fatigue, nausea or vomiting. Although 5-hydroxytryptophan did not elicit a positive effect on ADHD traits,further work should be conducted with measures more sensitive to ADHD traits to fully understand the impact of 5-hydroxytryptophan supplementation on the condition.